Prostaglandins and the mechanism of analgesis produced by aspirin-like drugs - Ferreira, S. H. (1973)
1. Resting splenic venous outflow from anaesthetized dogs contains prostaglandin-like material: the concentration increases after intra-arterial injections of bradykinin into the spleen, and is abolished by treatment with indomethacin. 2. Intra-arterial injections of bradykinin into the spleen of lightly anaesthetized dogs elicit a dose-dependent reflex increase in the blood pressure, which is reduced but not abolished by treatment with indomethacin. 3. Addition of prostaglandin E(1) or E(2) either by injections or by infusions restores the reflex increase in the blood pressure due to bradykinin injections after indomethacin treatment. 4. The sensitizing action of endogenously released prostaglandins at or near the afferent nerve endings is discussed. 5. The analgesic activity of aspirin-like drugs is explained in terms of the removal of the sensitizing activity of prostaglandins.